Optimization of a hydrogen liquefaction process utilizing mixed refrigeration considering stages of ortho-para hydrogen conversion. (5th May 2022) - Sun, Heng; Geng, Jinliang; Wang, Chao; Rong, Guangxin; Gao, Xiaoyu; Xu, Jiaming; Yang, Dacong
Abstract: The ortho-to-para hydrogen conversion (OPC) is an integral part of the hydrogen liquefaction process. The optimal stages and conversion temperatures of OPC are important to reduce the specific energy consumption (SEC) of the process. However, a limited number of studies directly discuss this aspect of the effect of the OPC stages on the SEC. Therefore, based on an efficient refrigeration liquefaction cycle, this paper analyzes the effect of different OPC stages on the SEC of the efficient refrigeration cycle. Additionally, the impact of different combinations of conversion temperatures for the same OPC stages on the SEC is investigated. Results are obtained using a process model developed in HYSYS V10 and the particle swarm optimization algorithm in MATLAB. The results show the impact of OPC stages on the SEC, and that the increase in the stages of OPC can reduce the SEC, but the reduction tends to be slow. The SEC of the five-stage OPC process decreases by 16.39% compared to the SEC of the one-stage. Furthermore, the reduction of SEC for the process with the same stages of OPC can be achieved by setting the optimal combinations of conversion temperatures, which can reduce the SEC by up to 10.63%. The results of this study demonstrate that optimizing the OPC stages is important to reduce the SEC and will provide valuable information for the design of OPC for hydrogen liquefaction processes. Highlights: The SEC decreases with increasing OPC stages, and the SEC for five-stage OPC is 16.39% lower than that for one-stage. The SEC under the same OPC stage can be reduced up to 10.63% by setting the conversion temperatures appropriately. The SEC under the same OPC stage is extremely influenced by the temperature of a particular conversion node.